On the Horn system of partial differential equations and series of hypergeometric type - Sadykov, T. M. (MATHEMATICA SCANDINAVICA, 2002)
The paper deals with the Horn system of hypergeometric differential equations. We consider the associated $\mathcal{D}$-module and construct an explicit basis in the space of holomorphic solutions to the Horn system under some assumptions on its parameters.